2021
DOI: 10.3390/molecules26144123
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Rice Straw via Hydrotropic Lignin Extraction and Its Characterization

Abstract: Rice straw hydrotropic lignin was extracted from p-Toluene sulfonic acid (p-TsOH) fractionation with a different combined delignification factor (CDF). Hydrotropic lignin characterization was systematically investigated, and alkaline lignin was also studied for the contrast. Results showed that the hydrotropic rice straw lignin particle was in nanometer scopes. Compared with alkaline lignin, the hydrotropic lignin had greater molecular weight. NMR analysis showed that β-aryl ether linkage was well preserved at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…9b). 122 The authors discussed the correlation between delignification reaction rate and CDF. The higher CDF signified the overall severity of the reaction, and the result showed that the lignin removal leveled at large CDF values.…”
Section: P-toluenesulfonic Acid (P-tsoh)mentioning
confidence: 99%
See 2 more Smart Citations
“…9b). 122 The authors discussed the correlation between delignification reaction rate and CDF. The higher CDF signified the overall severity of the reaction, and the result showed that the lignin removal leveled at large CDF values.…”
Section: P-toluenesulfonic Acid (P-tsoh)mentioning
confidence: 99%
“…128 The method showed high extraction efficiency (78%) and purity (78%) of the separated lignin. Freeze-thaw leads to effective lignin separation 122 while preventing oxidative degradation of lignin and hemicellulose dissolution. Consequently, the process yields highpurity lignin with elevated molecular weight.…”
Section: P-toluenesulfonic Acid (P-tsoh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PULCON method has demonstrated its advantages over other standard techniques in quantifying small molecules, 12,16 organometallic reagents, 17 and biological extract and metabolites, 11,14 its application to polymer quantification, except for occasional use in determining lignin concentration in foods, 18,19 in the context of drug delivery systems with the objective of establishing a straightforward and accurate protocol for physicochemical and pharmaceutical characterizations. Initially, the reliability and sensitivity of the PULCON protocol were assessed by examining samples with known concentrations of different polymers, either in combination or as single solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although the PULCON method has demonstrated its advantages over other standard techniques in quantifying small molecules, , organometallic reagents, and biological extract and metabolites, , its application to polymer quantification, except for occasional use in determining lignin concentration in foods, , remains largely unexplored. In this work, we investigate the applicability of the PULCON method in the context of drug delivery systems with the objective of establishing a straightforward and accurate protocol for physicochemical and pharmaceutical characterizations.…”
Section: Introductionmentioning
confidence: 99%